Albumin nano-encapsulation of caffeic acid phenethyl ester and piceatannol potentiated its ability to modulate HIF and NF-kB pathways and improves therapeutic outcome in experimental colitis - Tambuwala, Murtaza M. (Drug Deliv Transl Res, 2018)
Hypoxia inducible factor and nuclear factor-kappa beta pathways have been proposed as therapeutic targets for several inflammatory diseases. Caffeic acid phenethyl ester (CAPE) and piceatannol (PIC) are natural anti-inflammatory compounds; however, poor bioavailability and limited understanding of biomolecular mechanistic limits its clinical use. The aims of this study are to enhance bioavailability and investigate their impact on nuclear p65 and HIF-1α for the first time in experimental colitis. Dextran sulphate sodium was used to induce colitis in mice and effect of either free CAPE/PIC or CAPE/PIC loaded albumin nanoparticles treatment was observed on disease development and levels of cellular p65 and HIF-1α. Our results indicate that albumin nano-encapsulation of CAPE/PIC not only enhances its anti-inflammatory potential but also potentiates its ability to effectively modulate inflammation related biomolecular pathways. Hence, combining nanotechnology with natural compounds could result in development of new therapeutic options for IBD. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13346-018-00597-9) contains supplementary material, which is available to authorized users.